Optical and electrochemical properties of thermostable polymers containing light‐emitting units. Issue 5 (13th June 2013) - Damaceanu, Mariana‐Dana; Jarzabek, Bozena; Bruma, Maria
<x xml:space="preserve">Abstract</x> Two series of polymers and copolymers containing oxadiazole units have been studied with respect to their photo‐optical and electrochemical behavior. Fluorene units were introduced in the macromolecular chain together with oxadiazole rings in order to obtain a better balance between electrons and holes injection and transporting properties. Upon irradiation with UV light the polymers showed photoluminescence maxima in the blue spectral range. Cyclic voltammetry was performed in order to obtain information about the electrochemical stability and reversibility of the redox processes of these polyoxadiazoles. The highest occupied molecular orbital and lowest unoccupied molecular orbital energy levels, and electrochemical and optical band gap values were calculated by using the results of cyclic voltammetry and UV/vis spectroscopy, respectively, showing very good electron injection and transport characteristics. POLYM. ENG. SCI., 54:1126–1133, 2014. © 2013 Society of Plastics Engineers